2014
DOI: 10.1002/jcp.24554
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal ATF3 RNA Attenuates Pro‐Inflammatory Gene MCP‐1 Transcription in Renal Ischemia‐Reperfusion

Abstract: Transcriptional repressor activating transcription factor 3 (ATF3) is induced by various stress stimuli, including inflammation-induced renal injury. In addition, ATF3 also down-regulates adhesion molecules like intercellular adhesion molecule (ICAM), vascular cell adhesion molecule (VCAM), and monocyte chemotactic protein-1 (MCP-1). However, the relation between up-regulated ATF3 after renal ischemia/reperfusion (I/R) injury and MCP-1 is not completely understood. In this study, we demonstrated that, in renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 39 publications
(56 reference statements)
3
61
0
Order By: Relevance
“…For example, ATF1 is involved in wound healing and gingival inflammation [65]. ATF3 attenuates transcription of the proinflammatory gene MCP-1 in renal ischemia-reperfusion injury [14] and may significantly influence inflammatory processes in the central nervous system (CNS) that are related to the frequency of epileptic seizures [66]. Recent evidence suggests a role for ATF2 in inflammation.…”
Section: Functional Involvement Of Atf2 In Inflammationmentioning
confidence: 99%
“…For example, ATF1 is involved in wound healing and gingival inflammation [65]. ATF3 attenuates transcription of the proinflammatory gene MCP-1 in renal ischemia-reperfusion injury [14] and may significantly influence inflammatory processes in the central nervous system (CNS) that are related to the frequency of epileptic seizures [66]. Recent evidence suggests a role for ATF2 in inflammation.…”
Section: Functional Involvement Of Atf2 In Inflammationmentioning
confidence: 99%
“…Hence, urine exosome is an interesting source of urine biomarkers [1719]. Activating transcription factor 3 (ATF3) is one of the transcriptional factor protected inside urine exosome which expressed in urine of AKI in patients and animal models [20, 21]. Renal ATF3 is activated in mouse models of ischemic reperfusion injury and cisplatin induced nephrotoxicity [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Renal ATF3 is activated in mouse models of ischemic reperfusion injury and cisplatin induced nephrotoxicity [22, 23]. Interestingly, ATF3 downstream functions are anti-apoptosis and anti-inflammation through the attenuation of pro-inflammatory mediators and the alteration of the chromatin binding site in transcriptional factors [21, 22, 24, 25]. Hence, ATF3 should be involved in the pathophysiology of sepsis, AKI and sepsis-AKI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miRNA content of these vesicles seems to have a positive effect on renal tubular epithelial cells, reducing apoptosis and promoting cell proliferation [130]. Chen et al [131] probed, in a mouse model, that injection of exosomal transcriptional repressor activating transcription factor 3 (ATF3), which has an anti-apoptotic effect and inhibits inflammatory responses, is able to reduce ischemia-reperfusion kidney injury. Similarly, the effect of liver stem cell EVs in the regeneration of renal-tubule injury has been suggested in the study of Herrera Sánchez et al [132], who demonstrated the inhibitory effect of these vesicles on renal-tubular cell apoptosis in a murine model of acute kidney injury.…”
Section: Future Researchmentioning
confidence: 99%